DO RISK, BUSINESS CYCLE, AND COMPETITION AFFECT CAPITAL BUFFER? AN EMPIRICAL STUDY ON ISLAMIC BANKING IN ASEAN AND MENA - Maharani, Novita Kusuma; Setiyono, Bowo (Journal of Islamic Monetary Economics and Finance, 2018)
Basel III guidelines were released in 2010 by the Basel Committee on Banking Supervision (BCBS) as a revision of the previous Basel guidelines with the aim of strengthening the bank's capital and liquidity of banks. BCBS formulate a new policy that is the capital buffer. Capital Buffer is the difference between the minimum capital required by regulators with its overall capital and is considered a "cushion" against the shocks of the financial crisis. This study examine the impact of risk, business cycle, and competition on banks’ capital buffer. This paper used the sample of Islamic banks and conventional banks in ASEAN and MENA in the period 2011-2015 with unbalanced panel data. Using System GMM method to test the characteristics of Islamic banks in managing its capital. The finding indicates that the degree of capital buffer in islamic banks tend to adjust its risk. The result also shows that capital buffer decrease during economic expansion where banks act aggressively by extending their lending activities. The relationship between capital buffer and competition is positive in that the high level of competition to motivate banks to have higher capital.